The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.22159/ijap.2021.v13s4.43854
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Characterization of Serum Collagen of Sea Cucumber Extract Stichopus Horrens as an Antioxidant

Abstract: Objective: The study was aimed to extract, formulate and characterize collagen extract of Stichopus horrens into serum preparations and decide antioxidant activity in powders and serum preparations. Methods: The sea cucumber meat was extracted collagen in three stages, namely the pretreatment stage using 0.3 M NaOH solution 1:10 (w/v) for 48 h, the hydrolysis step in the 0.3 M 1:10 acetic acid solution (w/v) for 48 h, and the extraction stage with distilled water 1: 2 (w/v) for 2 h at 45 °C. The collagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…The gamat gel from Stichopus horrens sea cucumber, produced by PT GnE HMP Indonesia and containing 25% sea cucumber extract, demonstrated very low antioxidant activity with an IC50 value of 2937.5 ppm, equivalent to 20.7 ppm of ascorbic acid. This is better than a previous study of sea cucumber collagen serum, which showed an IC50 value of 4045.37 ppm (Stiani et al, 2021). The antioxidant activity in sea cucumbers is influenced by components such as peptides and certain salt compounds, although polyphenols also contribute significantly (Zhong et al, 2007).…”
Section: Hydrolytic Stabilitycontrasting
confidence: 60%
“…The gamat gel from Stichopus horrens sea cucumber, produced by PT GnE HMP Indonesia and containing 25% sea cucumber extract, demonstrated very low antioxidant activity with an IC50 value of 2937.5 ppm, equivalent to 20.7 ppm of ascorbic acid. This is better than a previous study of sea cucumber collagen serum, which showed an IC50 value of 4045.37 ppm (Stiani et al, 2021). The antioxidant activity in sea cucumbers is influenced by components such as peptides and certain salt compounds, although polyphenols also contribute significantly (Zhong et al, 2007).…”
Section: Hydrolytic Stabilitycontrasting
confidence: 60%